2019
DOI: 10.3389/fmicb.2019.00683
|View full text |Cite
|
Sign up to set email alerts
|

Actinobacteria Isolated From Laminaria ochroleuca: A Source of New Bioactive Compounds

Abstract: Nature is the major reservoir of biologically active molecules. The urgent need of finding novel molecules for pharmaceutical application is prompting the research of underexplored environments, such as marine ecosystems. Here, we investigated cultivable actinobacteria associated with the macroalgae Laminaria ochroleuca and assessed their potential to produce compounds with antimicrobial or anticancer activities. A specimen of L. ochroleuca was collected in a rocky… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(57 citation statements)
references
References 54 publications
1
56
0
Order By: Relevance
“…The MIC 90 values of the metabolites from some of the recently reported Streptomyces spp. against the strains of S. aureus and MRSA were in the ranges of 2–125 μg/mL [ 52 , 53 , 54 ], which indicated wide variation in the anti-bacterial potency of the metabolites. The results of the present study clearly demonstrated that the anti-bacterial potency of ADR1 metabolites appeared at the bottom of the range or even lower, validating its promising potential for discovery of drugs against priority pathogens.…”
Section: Resultsmentioning
confidence: 99%
“…The MIC 90 values of the metabolites from some of the recently reported Streptomyces spp. against the strains of S. aureus and MRSA were in the ranges of 2–125 μg/mL [ 52 , 53 , 54 ], which indicated wide variation in the anti-bacterial potency of the metabolites. The results of the present study clearly demonstrated that the anti-bacterial potency of ADR1 metabolites appeared at the bottom of the range or even lower, validating its promising potential for discovery of drugs against priority pathogens.…”
Section: Resultsmentioning
confidence: 99%
“…Certain bacteria which are beneficial in chemotherapy have been identified. For instance, Bacteroides [54], Deferribacteres [55], Tenericutes [56], and Actinobacteria [57] were indicated to be of beneficial for chemotherapy patients. At the genus level, Prevotellaceae_UCG-001 [58] and Rikenellaceae_RC9_gut_group [59] are involved in the degradation of carbohydrates and proteins to produce various organic acids.…”
Section: Discussionmentioning
confidence: 99%
“…These phytohormones have been tested on eggplant (Solanum melongena) and have improved the agronomic performance of the species. On the other hand, Endophytic Actinobacteria produces secondary metabolites that improve growth and resistance to various environmental stresses (Girão et al, 2019). For instance, kasugamycin and mildiomycin from Streptomyces kasugaensis and S. rimofaciens BOX 1 | Importance of P in live and role of bacteria to its availability Phosphorus is considered as the second most vital plant nutrient as well as second most deficient after nitrogen (Leghari et al, 2016).…”
Section: Potential Features Of Phosphate Solubilizing Actinobacteriamentioning
confidence: 99%